SUMBER DAYA MANUSIA PEREMPUAN INDONESIA - Endang Ediastuti Mustar (Populasi, 2007)
Women are a unique creature, in life they perform double fuction, as production and reproduction fuction. The number of women in Indonesia can be used as an important labor force, unfortunately they usually have lower level of education level. This at the end forced them to go abroad and being TKW which not always a good thing to do. Most of them being abused by their employers. Even though some women do not work economicly they still taking care their families which also an uneasy job to do. In the future, the empowerment of women could produce more quality generation.